2022
DOI: 10.1021/acs.langmuir.2c02303
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nanobubble Size and Stability on Ultrasound Enhanced Drug Delivery

Abstract: Lipid-shelled nanobubbles (NBs) are emerging as potential dual diagnostic and therapeutic agents. Similar to their micron-scale counterparts, microbubbles (1–10 μm), they can act as ultrasound contrast agents as well as locally enhance therapeutic uptake. Recently, it has been shown that the reduced size of NBs (<1 μm) promotes increased uptake and accumulation in tumor interstitial space, which can enhance their diagnostic and therapeutic performance. However, accurate characterization of NB size and concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Tethering of the MB sample after HIFU treatment led to a shift of ∼12 Hz, in which the increase in magnitude again can be attributed to removal of gas-filled MBs from the sample. It should be noted that MB samples likely also contain a proportion of submicrometer bubbles (i.e., nanobubbles) ,, that would also be able to interact with the SLB using the cDNA tethers. However, our recent work has shown that the HIFU treatment is also capable of inducing NB destruction …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tethering of the MB sample after HIFU treatment led to a shift of ∼12 Hz, in which the increase in magnitude again can be attributed to removal of gas-filled MBs from the sample. It should be noted that MB samples likely also contain a proportion of submicrometer bubbles (i.e., nanobubbles) ,, that would also be able to interact with the SLB using the cDNA tethers. However, our recent work has shown that the HIFU treatment is also capable of inducing NB destruction …”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that MB samples likely also contain a proportion of submicrometer bubbles (i.e., nanobubbles) ,, that would also be able to interact with the SLB using the cDNA tethers. However, our recent work has shown that the HIFU treatment is also capable of inducing NB destruction …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations